GSK3 beta and Erk are activated downstream of PI3K in synaptic endings during oxidative injury - Uranga, Romina Maria (2008)
Iron induced oxidative injury is comparable to that of ß-amyloid peptide on the brain of Alzheimer’s disease patients. Our purpose was to evaluate the state of PI3K pathway and its downstream effectors Akt and GSK3ß in cerebral cortex synaptosomes exposed 2+ to Fe (50 µM) for different periods of time (5, 30 and 60 min). The increase in Akt phosphorylation in serine 473 and threonine 308 was temporally coincident with PI3K activation (5 min). GSK3ß, the downstream effector of Akt, was also phosphorylated after 5 and 30 min of iron exposure and this phosphorylation was inhibited by LY294002. Additionally, Erk activation was also observed after 5 and 30 min of insult exposure, and this activation was PI3Kdependent. Immunoprecipitations carried out with anti-cSrc demonstrated a strong association between activated Akt and this tyrosine kinase induced by oxidative stress. Our results demonstrate that oxidative stress triggers the activation of different synaptic signaling pathways that operate downstream PI3K/Akt